Selection and Influence: A Meta-Analysis of the Association Between Peer and Personal Offending - Gallupe, Owen (Journal of quantitative criminology, 2019)
Whether people are affected by the criminal behavior of peers (the "influence" perspective) or simply prefer to associate with others who are similar in their offending (the "selection" perspective) is a long-standing criminological debate. The relatively recent development of stochastic actor-oriented models (SAOMs—also called SIENA models) for longitudinal social network data has allowed for the examination of selection and influence effects in more comprehensive ways than was previously possible. This article reports the results of a systematic review and meta-analysis of studies that use SAOMs to test for peer selection and influence effects.